The fungus Escovopsis (Ascomycota: Hypocreales): a critical review of its biology and parasitism of attine ant colonies - Elliot, Simon Luke; Montoya, Quimi Vidaurre [UNESP]; Caixeta, Marcela Cristina Silva; Rodrigues, Andre [UNESP] (Frontiers, 2024)
Two biological phenomena that contribute to increasing complexity in biological systems are mutualistic symbiotic interactions and the evolution of sociality. These two phenomena are also of fundamental importance to our understanding of the natural world. An organism that poses a threat to one or both of these is therefore also of great interest as it represents a challenge that mutualistic symbioses and social organisms have to overcome. This is the case with the fungus Escovopsis (Ascomycota: Hypocreales), which attacks the fungus garden of attine ants (Formicidae: Attina) such as the leaf cutters. This parasite has attracted much high-profile scientific interest for considerable time, and its study has been fruitful in understanding evolutionary, ecological and behavioural processes. Despite this, much of the biology and ecology of this organism remains unknown. Here we discuss this fungus and three sister genera (Escovopsioides, Luteomyces and Sympodiorosea) that until recently were considered as a single group. We first describe its position as the most highly specialised microbial symbiont in this system other than the mutualistic fungal cultivar itself and as that of greatest scientific interest. We then review the taxonomic history of the group and its macroevolution and biogeography. We examine what we know of its life cycle in the field – surprisingly little is known of how it is transmitted between colonies, but we explain what is known to date. We then review how it interacts with its host(s), first at the level of its direct interaction with the basidiomycete host fungi wherein we show the evidence for it being a mycoparasite; then at the colony level where empirical evidence points towards it being a parasite with a very low virulence or even merely a opportunist. Finally, we offer directions for future research.
Keywords: ecology; evolution; fungi; fungus-cultivating insects; host-parasite interactions; leafcutter ants; mycoparasitism; virulence